Ambidextrous leadership and innovation performance in MSMEs: balancing exploration and exploitation - Dina Noval Madurani; Muhammad Karisma Alam; Nadya Kariza (IICET (Indonesian Institute for Counseling, Education and Therapy), 2025)
While crucial for Micro, Small, and Medium Enterprise (MSMEs) survival and growth, innovation drivers like ambidextrous leadership remain relatively understudied in this context, particularly concerning the distinct roles of opening (OBL) and closing (CBL) leadership behaviors. This study aims to examine the distinct influences of closing behavior leadership (CBL) and opening behavior leadership (OBL) on innovation performance within Indonesian MSMEs. Employing a quantitative, cross-sectional survey design, data were collected from 115 employees across various Indonesian MSMEs, characterized predominantly by young workers with high school education. Data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings reveal that both CBL (β = 0.174, p = 0.018) and OBL (β = 0.509, p < 0.001) significantly and positively influence innovation performance. Notably, the impact of OBL was found to be substantially stronger than that of CBL in driving innovation performance within this sample. This research validates the applicability of ambidextrous leadership theory in the vital MSMEs sector and provides practical insights for MSME leaders, suggesting that while both structuring and creativity-enhancing behaviors are beneficial, fostering opening behaviors appears particularly crucial for maximizing innovation outcomes in these enterprises.